1970
DOI: 10.1113/jphysiol.1970.sp009021
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic control of adrenaline secretion in response to insufficient glucose

Abstract: SUMMARY1. The rise of plasma glucose consequent upon the release of adrenaline following the systemic administration of 3-O-methylglucose is prevented by previous infiltration with lignocaine of the lateral hypothalamic area on both sides.2. The similarity between this effect and that of the same procedure in preventing the hypersecretion of gastric acid in response to the same stimulus, together with the known fact that hypoglyeaemia or the systemic administration of some glucose analogues produce both gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(28 citation statements)
references
References 8 publications
2
26
0
Order By: Relevance
“…In previous studies we performed hypoglycemic clamp studies in bilaterally VMH lesioned rats as well as in rats with lesions in different brain areas (6). A marked inhibition of both the glucagon and catecholamine response to hypoglycemia was evident only in the VMH-lesioned animals, consistent with earlier studies implicating the hypothalamus in the activation of hypoglycemic counterregulation (13)(14)(15).…”
Section: Discussionsupporting
confidence: 66%
“…In previous studies we performed hypoglycemic clamp studies in bilaterally VMH lesioned rats as well as in rats with lesions in different brain areas (6). A marked inhibition of both the glucagon and catecholamine response to hypoglycemia was evident only in the VMH-lesioned animals, consistent with earlier studies implicating the hypothalamus in the activation of hypoglycemic counterregulation (13)(14)(15).…”
Section: Discussionsupporting
confidence: 66%
“…Morgane described a similar result in rats with lesion of the far-lateral hypothalamic area, attributing this effect to impairment of metabolic functions independently from that of food intake. Interference with metabolic functions by the lateral hypothalamus was demonstrated by Himsworth (1970), who found that lesions in this area reduces release of catecholamines from adrenal medulla in cytoglucopoenic rats, and by Teixeira, Antunes-Rodrigues & Migliorini (1973), who showed a decrease in peripheral mobilization of fatty acids in the same condition.…”
Section: Discussionmentioning
confidence: 96%
“…Although several lines ofevidence strongly implicate the CNS in hypoglycemia detection and counterregulation ( 1-3), the precise brain regions involved are not known. While various nuclei have been implicated, current data suggest that counterregulatory responses during hypoglycemia are activated, at least in part, via the hypothalamus (4)(5)(6). It has been frequently suggested that ventromedial hypothalamus (VMH),' known as a regulator of food intake ("satiety center") (7,8), may also contain glucosensitive tissues that could mediate the responses to hypoglycemia (9,10).…”
Section: Introductionmentioning
confidence: 99%